2005
DOI: 10.1002/humu.20156
|View full text |Cite
|
Sign up to set email alerts
|

Misprocessing of theCFTRprotein leads to mild cystic fibrosis phenotype

Abstract: Cystic fibrosis (CF) is mainly caused by mutations that interfere with the biosynthetic folding of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel. The aim of this study was to determine the mechanism of dysfunction of a disease-causing mutation associated with variable phenotypes. In order to attain these objectives, we studied the effect of the p.L206W mutation on CFTR protein production and function, and we examined the genotype-phenotype correlation of [p.L206W]+[p.F508del] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…Clain et al 25 analyzed 36 clinical cases of CF patients who were compound heterozygous for L206W and a severe CF mutation. Twelve of the cases were from the authors' own data, whereas the other 24 cases were obtained from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Clain et al 25 analyzed 36 clinical cases of CF patients who were compound heterozygous for L206W and a severe CF mutation. Twelve of the cases were from the authors' own data, whereas the other 24 cases were obtained from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a strong correlation between genotype and exocrine pancreatic function. They also showed that the milder mutation has a dominant phenotypic effect [9,10]. Thus, patients abhorring severe mutation on both alleles were classified as "severe" while patients having as least one allele associated with a milder phenotype were classified as "moderate to mild" (http://www.genet.…”
Section: Cf Status and Anthropometric Datamentioning
confidence: 99%
“…The severity of CF-related lung disease is highly variable, even among individuals bearing the same mutations, indicating that the disorder is influenced by complex, hereditary, and environmental factors (6,7). Similarly, marked variability in the severity of gastrointestinal and pulmonary disorders is observed among various strains of mice bearing CFTR mutations (8).…”
mentioning
confidence: 99%